BRIDGING THE LOGICAL GAP: VISUAL SCRIPTING AS A SCAFFOLDING STRATEGY FOR PHYSICS-BASED GAME DEVELOPMENT IN ENGINEERING EDUCATION. - Villagómez-Palacios, Álvaro; De la Fuente-Burdiles, Claudia; Vidal-Silva, Cristian (Scientific Culture, 2026)
The acquisition of computational thinking and programming proficiency represents a significant bottleneck for novice engineering students. Traditional syntax-heavy languages often impose a steep cognitive load that hinders the understanding of core algorithmic concepts. This study explores the efficacy of node-based visual programming environments, specifically Unity Visual Scripting, as a pedagogical scaffolding mechanism. By shifting the instructional focus from syntax memorization to visual logic flows, we aimed to enhance student engagement and technical competency. Utilizing a quasi-experimental design with a within-subjects approach ($N=22$), we analyzed development efficiency, academic performance, and code complexity. Results demonstrate that the visual paradigm facilitated a smoother transition to complex logic implementation, reducing development time by 30-50% for core mechanics and significantly improving student confidence. Crucially, participants identified Visual Scripting not as a replacement, but as a cognitive bridge that facilitates the understanding of algorithmic logic before tackling syntactic complexities.